Synthesis and evaluation of a novel quinoline-triazole analogs for antitubercular properties via molecular hybridization approach. Issue 20 (15th October 2019) - Ramprasad, Jurupula; Kumar Sthalam, Vinay; Linga Murthy Thampunuri, Rama; Bhukya, Supriya; Ummanni, Ramesh; Balasubramanian, Sridhar; Pabbaraja, Srihari
Graphical abstract: Abstract: Towards a quest for establishing new antitubercular agents, we have designed new quinoline–triazole hybrid analogs in a six-step reaction sequence involving versatile reactions like Vilsmeier–Haack and click reaction protocol. The design is based on the structural modification of bedaquiline moiety and involves molecular hybridization approach. The structure of the synthesized product was elucidated by single crystal X-ray diffraction study. The synthesized target compounds were screened for their antitubercular activity against Mycobacterium bovis . Interestingly, two compounds of the series (8d and 8m ) showed significant inhibition with MIC of 31.5 and 34.8 μM. Compounds bearing 3-fluoro phenyl and n -octyl groups on the 1, 2, 3-triazole ring emerged as the most potent leads among the compounds tested. Further these hit compounds were also screened for their cytotoxic effect on human embryonic kindey 293 (HEK293) cells and other cancer cell lines such as HeLa (Cervical), PC3 (Prostate), Panc-1 (Pancreatic) and SKOV3 (Ovarian) indicating to be safer with the minimal cytotoxicity.